Biomaterial applications in neural therapy and repair. Issue 1 (December 2016) - Ghuman, Harmanvir; Modo, Michel
Abstract The use of biomaterials, such as hydrogels, as a scaffold to deliver cells and drugs is becoming increasingly common to treat neurological conditions, including stroke. With a limited intrinsic ability to regenerate after injury, innovative tissue engineering strategies have shown the potential of biomaterials in facilitating neural tissue regeneration and functional recovery. Using biomaterials can not only promote the survival and integration of transplanted cells in the existing circuitry, but also support controlled site specific delivery of therapeutic drugs. This review aims to provide the reader an understanding of the brain tissue microenvironment after injury, biomaterial criteria that support tissue repair, commonly used natural and synthetic biomaterials, benefits of incorporating cells and neurotrophic factors, as well as the potential of endogenous neurogenesis in repairing the injured brain.